Grid-tied inverter for solar power using Gallium Nitride (GaN) devices - part I hardware - Chen, Wei (2014)
The development of this project was divided mainly into two parts, the design of dc-ac inverter including Prism based simulation and hardware production, and the hardware inverter protection including Matlab based power loss simulation and heat sink selection regarding to the simulated power loss results. The original project object was using GaN switch to design the inverter. However, the GaN switch was unable to be delivered in hardware production, and IGBT switch was to be used instead. Since the GaN switch is capable of producing more than MHz leveled frequency, the Prism based simulation for GaN was conducted and investigated corresponding to the inductor. In general, the objectives of this project was successfully delivered.